واقع استخدام تكنولوجيا السبورة الذكية يف معاهد العلوم اإلسالمية بسلطنة عمان The reality of using smart board technology in Islamic Science institutes in Oman - Said Aljabri, Abdullah Humaid; Sahrir, Muhammad Sabri (Scientific Institute of Advanced Training and Studies (SIATS), UK and KL, 2020)
This study aimed to reveal the reality of using smart-board technology in the Islamic institutes in the Sultanate of Oman. The study’s population consists of 80 teachers, all of them work at the Islamic Institutes in the Sultanate of Oman . The research was applied to the teachers in the institutes (67 teachers) selected in accordance with the intentional method of sampling.The researcher used the descriptive method. The data collection/research tool was designed and developed by the researcher. The research tool is a questionnaire consisting of six axes and 45 items. The results of the mathematical averages of the research questions showed, a medium degree of smart-board readiness (availability) for use in classrooms , and a large degree of challenges encountered by teachers in using smart-board. As for the teachers’ suggestions (proposed vision of implications) to develop smart-board use, holding workshops for teachers on how to make the best use of smart-board is revealed to be the most frequent response. Based on the results, the researcher recommended holding inductions and introductory workshops for teachers about smart-board and how to make the best use of it as one of the privileges available in the Islamic Institutes.